Anti-diarrhoeal activity of ethanolic extract of heartwood of Pterocarpus marsupium roxb. - Shridhar, Bhawna; Mani, Munesh; Kumar, Prevesh; Yadav, Shivansh; Mahaur, Kamal Kumar (Journal of Drug Delivery and Therapeutics, 2018)
Diarrhoea is a common cause of death in developing countries and second most common cause of infant’s death worldwide. Pterocarpus marsupium is a medicinal herb belonging to the family Fabaceae has been traditionally used in the treatment of diarrhoea. They were found to contain tannins, alkaloids, saponins, sterols, triterpenes and reducing sugars. This study evaluated the antidiarrhoeal activity of ethanolic extract of heartwood of Pterocarpus marsupium induced by castor oil and magnesium sulphate in rat at 200 and 400 mg/kg b.w. The doses were given orally and showed significant antidiarrhoeal activity comparable with that of the standard drug loperamide. The statistical analyses of results were carried out using one-way analysis (ANOVA) followed by Student t-test. On the basis of these ﬁndings, it can be assumed that Pterocarpus marsupium could be a potential source for novel discovery for antidiarrhoeal. These results may support the fact that this plant is used traditionally to cure diarrhoea. Keywords: Pterocarpus marsupium, Anti-Diarrhoeal, Castor Oil, Magnesium Sulphate, Loperamide